Peningkatan Hasil Belajar PPKn Melalui Strategi Pembelajaran Aktif Tipe Giving Question and Getting Answer Pada Peserta Didik Kelas V Sekolah Dasar - Selvinia, Riza (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The purpose of this research was to improve student learning outcomes in PPKn grade V elementary schools with  active learning strategy type Giving Question and Getting Answer (GQGA) . The research conducted was a Classroom Action Research (PTK) with three cycles, with each cycle consisting of one meeting. The stages of each cycle are planning, implementing, observing and reflecting. Each meeting is carried out formative test to determine the progress of students. In the first cycle the students who completed after carrying out the formative test were 70% and a class average 70. In the second cycle students who completed after carrying out the formative test were 82,5% dan a class average 77. In the third cycle students who completed after carrying out formative test were 100% and a class average 81,75. These results indicate that active learning strategy type giving question and getting answer (GQGA) can improve student learning outcomes, especially grade V PPKn at SD Negeri 04 Serang academic year 2019/2020.